ASPECTE PSIHOPEDAGOGICE ALE PROCESULUI DE ÎNVĂŢARE EFICIENTĂ A MATEMATICII ÎN LICEU - USM ADMIN (Moldova State University, 2010)
Psycho-pedagogical analysis of school work in mathematics identifies those capabilities that they must form the students to successfully adapt the school environment. The positive changes in students mental structures and functions and personality and their structures are determined by effective learning.